Random Laser Effect on a Bacterial Cellulose Aerogel using Rhodamine 6G as Gain Medium - da Silva Cruz, Marcelo; de Freitas, Beatriz D. [UNESP]; Marchiori, Leonardo [UNESP]; Pugina, Roberta S. [UNESP]; Ferreira-Neto, Elias P.; Pincheira, Pablo I.R.; Gomes, Anderson S.L.; Ribeiro, Sidney J.L. [UNESP]; De Boni, Leonardo (My University, 2024)
The Random Laser action was investigated on bacterial nanocellulose coated with SiO2 and TiO2 doped with RH6G. In samples of different thicknesses, a narrowing of the FWHM value and threshold lasing energy was both observed.